Type 2 diabetic patient-centered care - Somjit Prueksaritanond (2018)
Background: The prevalence of diabetes mellitus has increased worldwide including Thailand. Management of diabetes should be considered biological and psychosocial. Patient-centered care was applied in the present study. Patient-centered care is a process interaction between the clinician and the patient. It refers to the clinician's behavioral skill in the consultation. Patient-centered care customizes seeking and accepting the patient's ideas, seeking and giving recognition and encouragement, treatment recognition and decision making in response to the individual patient's perspective. Objective: To evaluate the efficacy of patient-centered care on type 2 diabetes mellitus. Their fasting plasma glucose (FPG), hemoglobin Alc (HbAlc), eating and exercise behavior, compliance, symptoms of diabetes as well as satisfaction were compared before and after the intervention. Material and Method: The quasi-experimental design (controlled before and after intervention)) was conducted among 78 patients with type 2 diabetes mellitus who regularly attended the outpatient clinic, Family Medicine Department, whose FPG was more than 150 mg/dL, non pregnant, could communicate well in Thai and had no other complications. The patients were required to follow on Wednesday morning every 6-10 weeks for one year. A group of 6-10 patients was appointed in each visit. The six interconnecting components of patient-centered care were applied. (1) The patients and the researchers were introduced to each other to enhance the relationship between the patients, doctors and researchers. (2) In each visit, by using a group process and individual approach, the authors explored, assessed and analyzed both the disease, the illness (patient's ideas, feelings, expectations and functions), drug compliance, eating and exercise behavior. (3) The patient's life, family history, psychological and social behaviors were emphasized (4) Setting the goals of FPG level that is achievable and agreeable to both the physician and patients, (5) Each patient was required to attend both nutrition and exercise education workshops. (6) Self care and self records on food items as well as nutrition and exercise practice were emphasized in order to incorporate them into their lifestyle. Results: There were 53 females (67.9%) and 25 males (32.1%). Average age was 57.2 years. Diabetes duration was 6.75 ± 5.45 years. Mean FPG of overall subjects decreased 43.07 ± 76.32 mg/dL. About 16.44% had FPG below 126 mg/dL. 55.13% retained the same hypoglycemic-medications, 10.5% had decreased dosage. Amongst 33 subjects (42.3%) who completed the program, FPG decreased 73.58 ± 70.99 mg/dL (p < 0.000). HbAlc decreased 0.92 ± 1.41% (p = 0.001). Eating behavior (p < 0.000) and exercise behavior (p < 0.05) were better. Symptoms of diabetes were improved. Patient's satisfaction indicated that they had a better understanding of the disease and illness. They were eager to share their experiences with others and able to develop a relationship with the health care team. Amongst 45 patients (57.7%) who partially followed the program, FPG decreased 39.55 ± 68.54 mg/dL (p = 0.001). Conclusion: Glycemic control of type 2 diabetes subjects was improved by patient-centered care, Eating and exercise behaviors, compliance, symptoms of diabetes were better. This pilot study showed that the health status was improved not only by the biological indicators but also by behavior. The present study provided a beneficial impact on improving the health status of type 2 diabetes.